2017
DOI: 10.1038/srep44486
|View full text |Cite
|
Sign up to set email alerts
|

ICOSL expression in human bone marrow-derived mesenchymal stem cells promotes induction of regulatory T cells

Abstract: Mesenchymal stem cells (MSCs) can modulate lymphocyte proliferation and function. One of the immunomodulatory functions of MSCs involves CD4+CD25+FoxP3+ regulatory T cells (Tregs), which negatively regulate inflammatory responses. MSC-mediated Treg induction is supposed to be regulated by mechanisms requiring both soluble and cell contact-dependent factors. Although the involvement of soluble factors has been revealed, the contact-dependent mechanisms in MSC-mediated Treg induction remain unclear. We attempted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 54 publications
2
54
1
1
Order By: Relevance
“…In contrast to the restriction of the CD28 and CTLA-4 ligands (CD80 and CD86) largely to lymphoid tissues, ICOSL is widely expressed on somatic cells (figure 1). It can be induced by tumour necrosis factor-α on many non-lymphoid cells including endothelial cells, lung epithelial cells, fibroblasts, mesenchymal stem cells and tumour cells 11–15…”
Section: Icos Biologymentioning
confidence: 99%
“…In contrast to the restriction of the CD28 and CTLA-4 ligands (CD80 and CD86) largely to lymphoid tissues, ICOSL is widely expressed on somatic cells (figure 1). It can be induced by tumour necrosis factor-α on many non-lymphoid cells including endothelial cells, lung epithelial cells, fibroblasts, mesenchymal stem cells and tumour cells 11–15…”
Section: Icos Biologymentioning
confidence: 99%
“…In this study, PGE2 and transforming growth factor beta (TGF‐β) were also mechanistically implicated, suggesting a combined role for contact‐dependent signals and soluble mediators. Subsequently, Lee et al reported that expression of inducible costimulator ligand (ICOSL/CD275) by human MSCs when cocultured with CD4 + T‐cells is essential for T‐reg induction under in vitro conditions as knockdown of ICOSL and use of transwell cultures significantly reduced T‐reg induction and IL‐10 production . Mesenchymal stromal cells also express a wide range of other surface adhesion molecules including integrins, vascular cell adhesion molecule (VCAM)‐1, intercellular adhesion molecules (ICAM‐1, ICAM‐2), CD72, and CD58 (LFA‐3), which have been shown to bind to T cells with very high affinity and to play important roles in immune suppression.…”
Section: Potential Mechanisms For Msc‐mediated Effects On T‐regmentioning
confidence: 99%
“…ICOS costimulation of CD4 + T cells favors the production of Th2 cytokines such as IL-4, IL-10, and IL-13 ( 11 ). Particularly, ICOS/ICOSL axis plays a crucial role in Treg cell function and promotes Treg differentiation through activating the phosphoinositide 3-kinase/Akt pathway ( 12 ). The finding that H.polyguras elicited Foxp3 + T cells were all negative for expression of Helios, a specific marker of thymic-derived Treg cells marker ( 13 ), and this population was absent in ICOS −/− mice, suggests that ICOS affects the induction of Treg cells predominantly in the periphery ( 14 ).…”
Section: Introductionmentioning
confidence: 99%